Решите уравнение (1-x)(2-x)=(x+3)(x-4) (2-x)(3-x)=(x+2)(x-5) выражение (2x+1)(x-1) (x+2)(2x-1)

marinavn2008 marinavn2008    2   30.05.2019 05:40    0

Ответы
mikki255 mikki255  01.10.2020 14:59
1)х равен 7 2)х равен 8
ПОКАЗАТЬ ОТВЕТЫ
voicehovakseneлеля voicehovakseneлеля  01.10.2020 14:59
 (1-x)(2-x)=(x+3)(x-4)
2-х-2х+х*х=х*х-4х+3х-12
2-3х=-х-12
-2х=-14
х=7
(2-x)(3-x)=(x+2)(x-5)
6-2х-3х+х*х=х*х-
5х+2х-10
6-5х=-3х-10
-5х+3х=-10-6 -2х=-16
Х=8
(2x+1)(x-1) (x+2)(2x-1)=(4х*х )(x-1) (x+2)=(4х*х)(х*х+х-2)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра